The Influence of Corporate Governance on the Performance of Islamic Banking Companies in Indonesia - Soveinia Soveinia; Hery Haryanto (Jurnal Ilmiah Ekonomi Islam, 2022)
The study examines the relationship between corporate governance as measured by audit committee independence, audit committee size, audit committee meetings, the board size, managerial ownership, and institutional ownership as well as control variables, namely firm size, firm age, and debt on firm performance as measured by ROA at the bank. general sharia law in Indonesia is registered with the financial services authority for the period 2013-2020. The research method using linear regression analysis, partial test, simultaneous test, and coefficient of determination found a significant effect of board size, firm size, and debt on the performance of Islamic banking companies. While other variables are independence, size, and audit committee meetings.